Hindu Kaharingan across Time: Anthropological Portrayals of a Religion in Transition Keynote Address: Hindu Kaharingan across Time: Anthropological Portrayals of a Religion in Transition Keynote Address - Anne Schiller (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2019)
The beliefs and religious practices of Kalimantan’s indigenous peoples have been documented by social scientists and others for well over a century. Hindu Kaharingan, however, is unique in the robust level of scientific attention that it has attracted. Anthropologists have had the privilege of investigating and analyzing part of Hindu Kaharingan’s unfolding story. The vitality of Hindu Kaharingan and its role in local identity continues to generate interest among Indonesian and foreign researchers alike. This presentation examines changes in how Kaharingan has been portrayed by anthropologists over time. It argues that the recognition of Hindu Kaharingan was a watershed moment in indigenous religious activism. Since that time, Hindu Kaharingan has often been cited as an example of a native religion that has survived and thrived in the face of social transformation. Yet, interest in Hindu Kaharingan is not limited to academicians only. In 1996, with the encouragement of local cultural activists, the National Geographic Society produced a television film about Kaharingan. While the film led to broader appreciation across the globe of Dayak culture, its production also raised complex issues regarding how controversial aspects of Ngaju death rituals should be portrayed. The presentation concludes with a call for new research, conducted by adherents of Hindu Kaharingan themselves and published in multiple languages in scientific journals with the highest peer review standards, to add more perspectives to this exceptional story of cultural survival and identity in contemporary Indonesia.